50th AIAA/ASME/SAE/ASEE Joint Propulsion Conference 2014
DOI: 10.2514/6.2014-3933
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Effects of High Turbulence Intensity on a Variable-Speed Power-Turbine Blade with Large Incidence and Reynolds Number Variations

Abstract: The effects of high inlet turbulence intensity on the aerodynamic performance of a variable speed power turbine blade are examined over large incidence and Reynolds number ranges. These results are compared to previous measurements made in a low turbulence environment. Both high and low turbulence studies were conducted in the NASA Glenn Research Center Transonic Turbine Blade Cascade Facility. The purpose of the low inlet turbulence study was to examine the transitional flow effects that are anticipated at cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The incidence angles that are presented apply to the take-off and cruise conditions for the VSPT project. 5 The blades and their nominal inlet flow vectors are shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…The incidence angles that are presented apply to the take-off and cruise conditions for the VSPT project. 5 The blades and their nominal inlet flow vectors are shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…In order to cope with the above-mentioned problems, the wide working condition power turbine blades are developing in the direction of highly-loaded, large incidence angle, and low Reynolds number state. The United States has carried out more in-depth research work in this research area, including high-precision calculation methods, 48,55 the influences of incidence angle, 56 inlet turbulence, 57–61 and Reynolds number effects, 62–64 etc. The specific research results can be found in related papers.…”
Section: Aerodynamics Of Variable Speed Power Turbines For Turboshaft...mentioning
confidence: 99%
“…The blades were attached to a disk that can be rotated to set inlet flow angles (from axial) in the range −17° ≤ β 1 ≤ +78.8°. During this test, ten incidence angles were examined 10,11 . Detailed three-dimensional flow field data were acquired at incidence angles of +5.8° (β 1 = +40.0°) and −36.7° (β 1 = −2.5°), which represent the cruise and takeoff flight mission points, respectively.…”
Section: Ii-vspt Blade Experimentsmentioning
confidence: 99%
“…Nearly laminar flow was obtained by running the tunnel without the turbulence grid. High tunnel free stream turbulence is obtained by utilizing an upstream blowing grid located roughly 5 axial chords upstream of the blade row 11 . Some of the high free stream turbulence conditions are also transitional.…”
Section: Ii-vspt Blade Experimentsmentioning
confidence: 99%